Religious Teachers' Views on The Caliphate Concept In The Learning Context - Ahmad Muthohar (Nadwa: Jurnal Pendidikan Islam, 2022)
The discourse on re-establishing the caliphate as a constitutional system has generated controversy. Such controversy has also penetrated the education context, including Islamic education. The research results indicated that the religious teachers' understanding of the caliphate has various thoughts. This difference will affect the learning method and students' understanding. In general, this variety of understanding can be categorized into three groups. First, the semi-group supports the caliphate, believing it will be established if each citizen improves their understanding of monotheism. The second is a neutral group. They stated that the implementation of the caliphate system had been practiced by socio-religious organizations in Indonesia, such as Nahdlatul Ulama or Muhammadiyah. The third is the counter group on the caliphate. This group views Indonesia as a country that can be interpreted as the incarnation of a caliphate with a democratic system; the president is also considered a caliph. These three groups of teachers with different understandings of the caliphate will affect students' understanding. If they are not straightened out, it will endanger the existence of the unitary state of the Republic of Indonesia as an established nation.